Report of the Surgeon General's Workshop on Healthy Indoor Environment January 12-13, 2005, National Institutes of Health, Bethesda, MD. - Surgeon General's Workshop on Healthy Indoor Environment (2005, National Institutes of Health); United States Public Health Service ([Rockville, Md.?] U.S. Public Health Service, Dept. of Health and Human Services, 2005)
The 2005 workshop was conducted to: 1. Enhance understanding of the public health consequences of the non-industrial indoor environment (e.g., homes, schools, office buildings); 2. Provide information to the U.S. Surgeon General, the public, the medical community, and the public health community; and 3. Provide the building design, construction, and ownership community with a better understanding of public health issues as they relate to the indoor environment. The stated goals and objectives of the workshop were to: 1. Seek collaboration throughout the public health community in reducing indoor environmentally related communicable respiratory infections, asthma, hypersensitivity pneumonitis, and allergic diseases; and 2. Gain a better understanding of public health issues and research needs on this topic
Title from PDF t.p. - Mode of access: Internet from the Surgeon General's web site. Address as of 2/12/09: http://www.surgeongeneral.gov/topics/indoorenv/pdf/HIEWorkshopBinder.pdf; current access available via PURL.
Keywords: Air Pollution, Indoor / adverse effects / https://id.nlm.nih.gov/mesh/D016902Q000009; Environmental Illness / https://id.nlm.nih.gov/mesh/D018876